Menerapkan Pemahaman Penyakit Influenza Pada Anak Usia Dini - Anisa Tahira; Rahma Sukmara Putri; Siska Prifiantari (UIN Sultan Maulana Hasanuddin Banten, 2022)
Health is the most important thing for every individual, an understanding of health is something that every individual must know, one of which is influenza. This study was designed with a qualitative method, namely the type of research that is descriptive and carried out by means of data analysts in accordance with the facts in the field, this method is a case study that collects data through observation, interviews, and surveys via google form, the aim is to find out the responses from young people in West Java, parents, children and the people of the village of Saguling. The results of this study are that parents, children and young people in the West Java area already understand what, how and how to deal with influenza, the average way they do to avoid influenza is to get enough rest and drink lots of water to increase immunity body. Keywords: Influenza, Health, early childhood References Al Adawiyah, R., & Priyanti, N. (2020). Pengaruh Peran Ayah Terhadap Adaptasi Sosial Pada Anak Usia Dini Di Yayasan Nurmala Hati Jakarta Timur. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(2), 155–168. Ardiaria, M. (2020). Peran Vitamin D Dalam Pencegahan Influenza Dan Covid-19. JNH (Journal of Nutrition and Health), 8(2), 79–85. Aulia, N., Kharis, M., & Supriyono. (2016). Pemodelan Matematika Epidemi Influenza Dengan Memperhatikan Peluang Keberhasilan Vaksinasi Dan Kekebalan Tetap. Unnes Journal of Mathematics, 5(2), 190–200. https://doi.org/ 10.15294/ujm.v5i2.13132 Burni, E., Dinihari, T. N., Saragih, R. M., Purwanto, E., Muhiriyah, E., Nugroho, G. W., Abdurahman, Puhilian, Wawang, Masfuufah, S., Malyati, Y., Wahyuriadi, R., Zubir, Y., Umar, B. N., Putra, B., Ratih, I. G., & Dll. (2020). Penyelidikan dan Penanggulangan Kejadian Luar Biasa Penyakit Menular dan Keracunan Pangan (Revisi 3). Kementerian Kesehatan Republik Indonesia. Handojo, I., Soeparyatmo, J., Wirawan, R., Sudewa, A., Pang, T., & Suryaatmaja, M. (2010). EPIDEMIOLOGI DAN DIAGNOSIS KEDOKTERAN LABORATORIK INFEKSI VIRUS H1N1 (The Epidemiologic and Medical Laboratoric Diagnosis of Viral Infection H1N1). CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 6, 105–151. Hidayat, M. , L. (2016). Virus Influenza, Penegur Antroposentrisme Manusia (Habib. A, Ed.). Adekom Sef-publishing house. Ikat, B., & Morgen, M. E. (2020). OPTIMASI FASILITAS BANDAR UDARA DOMESTIK KE BANDAR UDARA INTERNASIONAL TERHADAP FASILITAS LANDSIDE BANDAR UDARA INTERNASIONAL SYAMSUDIN NOOR BANJARMASIN. (Doctoral Dissertation, SEKOLAH TINGGI TEKNOLOGI KEDIRGANTARAAN YOGYAKARTA). Ikawati, H. D., Roselinda, R., Yekti, R. P., & Setiawaty, V. (2016). Predominant clinical symptom of influenza A in pre-school children (3-6 years old). Health Science Journal of Indonesia, 7(2), 80–83. https://doi.org/ 10.22435/hsji.v7i2.5473.80-83. Imroatun, I. (2015). Masjid dan Pengembangan Wawasan Aak Usia Dini dalam Pelestarian Lingkungan Hidup Nasional. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 5(1), 21–28. Imroatun, I., Nirmala, I., Juhri, J., & Muqdamien, B. (2020). Kajian Literatur Pengasuhan Anak Usia Dini Dalam Islam. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(1), 57–66. Maulana, N. (2010). Swamedikasi Terhadap Influenza Pada Masyarakat Di Kabupaten Karanganyar Tahun 2009. (Doctoral Dissertation, Universitas Muhammadiyah Surakarta). Nasrullah, A., Supriyono, & Kharis, M. (2013). Pemodelan Sirs Untuk Penyakit Influenza Dengan Vaksinasi Pada Populasi Manusia Dengan Laju Recruitment and Death. Unnes Journal of Mathematics, 2(1), 47–54. https://doi.org/10.15294/ujm.v2i1.1711. Nitiyoso, N. (2018). Antivirus untuk Influenza. 45(4), 261–264. Nuria, R. (2018). Pengembangan Modul Pembelajaran Hidup Sehat Anak Usia Dini Pada Taman Kanak-Kanak. Jurnal Golden Age, 2(2), 96–112. Nuryati, Muthmainnah, Talango, S. R., Ibrohim, B., & Nadjih, D. (2021). Metode Role Playing Dalam Meningkatkan Motivasi Berprestasi Anak Usia Dini Selama Masa Learning From Home. As-Sibyan (Jurnal Pendidikan Anak Usia Dini), 6(2), 139–145. Pertiwi, R., Ningsi, C. N., Wulandari, W., Tosepu, R., Masyarakat, J. K., Kesehatan, F., Universitas, M., Oleo, H., Tenggara, S., Masyarakat, J. K., Kesehatan, F., Universitas, M., Oleo, H., & Tenggara, S. (2020). Hubungan iklim dengan penyakit influenza: literatur review. 17(1), 27–32. Rosyidah, K. A., & Fanani, Z. (2021). GAMBARAN PENGETAHUAN DAN PERILAKU SWAMEDIKASI INFLUENZA PADA MASYARAKAT DI DESA PLADEN, KECAMATAN JEKULO, KUDUS. Indonesia Jurnal Farmasi, 5(2), 26–30. Starlista, V., Endarti, D., & Andayani, T. M. (2020). Tingkat Pengetahuan Orang Tua Terhadap Penyakit dan Vaksin Influenza di Indonesia. Jurnal Farmasi Sains Dan Praktis, 6(2), 125–133. https://doi.org/10.31603/ pharmacy.v6i2.3440. Suyanto, W. S., Purba, K. R., Studi, P., Informatika, T., Industri, F. T., Petra, U. K., & Surabaya, J. S. (n.d.). Pembuatan Aplikasi Media Pembelajaran Virus Infulenza Berbasis Flash. 1–6. Ulfadilah, N. , M. E. H. , & M. H. Y. (2021). Pemanfaatan Media Permainan Sains untuk Memfasilitasi Perkembangan Motorik Halus Anak. . PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 5(1), 49–58. Wahyuningtyas, F. (2010). Gambaran Swamedikasi Terhadap Influenza Pada Masyarakat Di Kabupaten Sukoharjo. (Doctoral Dissertation, Universitas Muhammadiyah Surakarta). Murniati, D., Giriputro, S., & Hadinegoro, S. R. S. (2011). Karakteristik Klinis dan Epidemiologis Avian Influenza A (H5N1) Anak Di Indonesia, Tahun 2005-2007. Sari Pediatri, 12(5), 347–358. https://doi.org/10.14238/ sp12.5.2011.347-58